The “Johannine Prayer” that Never Really Was - Watson, Murray K. (Studies in Christian-Jewish Relations, 2011)
Since 1965, a moving “prayer of contrition” for the sins of Catholics against Jews throughout the centuries has circulated in various forms and languages in numerous Jewish and Christian publications and Web sites. The prayer, allegedly composed by the dying Pope John XXIII for worldwide recitation, was already called into question in the 1960s by commentators close to the late Pope familiar with his writings. In more recent years, investigations into the authorship of the prayer have concluded with reasonable certainty that its origins actually lie with the Irish-born Jesuit priest and scholar Malachi Martin, a Vatican II insider whose concern for promoting Jewish-Catholic relations apparently extended to the point of “ghost-writing” this prayer. This article examines both the popularity and influence of this prayer, and some of the evidence that points to Martin (and not John XXIII) as its source.